ANALISIS KEPUASAN PENGGUNA SISTEM INFORMASI E-GOVERNMENT MENGGUNAKAN METODE WEBQUAL 4.0: Studi Kasus: Website Simsarpras Kementerian Agama - Frandika Septa; Rusydi Umar (METHOMIKA: Jurnal Manajemen Informatika & Komputerisasi Akuntansi, 2019)
The service of a government institution to the community through an electronic or E-Government based information system needs to be analyzed to the satisfaction of its users, to determine the quality of the information system services, especially if the service is a necessity and is considered important for community development. This study analyzes the quality of a site belonging to the Ministry of Religion, namely the website for information systems and infrastructure (SIMSARPRAS). The study was conducted to determine the quality of the SIMSARPRAS website based on user perceptions. The method used in this research is WebQual 4.0 with data analysis using multiple linear regression. The results of this study provide conclusions that partially and simultaneously all dimensions of the WebQual 4.0 method have a positive and significant effect on user satisfaction from the SIMSARPRAS website. The regression coefficient shows that the dimensions of service interaction quality give the greatest value to user satisfaction with a value of 0.451. The coefficient of determination shows that all WebQual 4.0 dimensions are able to influence user satisfaction by 64.8%, and it is concluded that the quality of SIMSARPRAS websites is in good quality.